Bedside interpretation of simplified continuous EEG after cardiac arrest. Issue 1 (2nd October 2019) - Lybeck, Anna; Cronberg, Tobias; Borgquist, Ola; Düring, Joachim Pascal; Mattiasson, Gustav; Piros, David; Backman, Sofia; Friberg, Hans; Westhall, Erik
Abstract : Background: Continuous EEG‐monitoring (cEEG) in the ICU is recommended to assess prognosis and detect seizures after cardiac arrest but implementation is often limited by the lack of EEG‐technicians and experts. The aim of the study was to assess ICU physicians ability to perform preliminary interpretations of a simplified cEEG in the post cardiac arrest setting. Methods: Five ICU physicians received training in interpretation of simplified cEEG ‐ total training duration 1 day. The ICU physicians then interpreted 71 simplified cEEG recordings from 37 comatose survivors of cardiac arrest. The cEEG included amplitude‐integrated EEG trends and two channels with original EEG‐signals. Basic EEG background patterns and presence of epileptiform discharges or seizure activity were assessed on 5‐grade rank‐ordered scales based on standardized EEG terminology. An EEG‐expert was used as reference. Results: There was substantial agreement (κ 0.69) for EEG background patterns and moderate agreement (κ 0.43) for epileptiform discharges between ICU physicians and the EEG‐expert. Sensitivity for detecting seizure activity by ICU physicians was limited (50%), but with high specificity (87%). Conclusions: After cardiac arrest, preliminary bedside interpretations of simplified cEEGs by trained ICU physicians may allow earlier detection of clinically relevant cEEG changes, prompting changes in patient management as well as additional evaluation by an EEG‐expert. This strategy requires awareness of limitations of both the simplified electrode montage and the cEEG interpretations performed by ICU physicians. cEEG evaluation by an expert should not be delayed.